Smartphone Addiction among Adolescence Students: Its Implication toward Family Communication, Learning, Guidance and Counselling - Atmoko, Adi; Sari, Indah Kartika; Augusto, , Da Costa; Utami, Nugraheni Warih; Wahyuni, Eny Tri (Jurnal Kajian Bimbingan dan Konseling, 2022)
The symptoms of smartphone addiction have been extensively observed in adolescent students. This study aims to investigate the effects of smartphone addiction on students’ communication with their families, their learning, as well as guidance and counseling processes. The causal correlational design was applied, involving 103 participants selected total samplings of eighth-graders junior high school students. The data was garnered through the smartphone addiction scale and family communication scale. Both of those scales had item validity of 0.3, with Alpha Cronbach reliability of 0.937 and 0.850, respectively. The obtained data were analyzed using regression. The analysis results suggest that smartphone addiction significantly decreased the quality of students’ communication with their families, by -0,416. This result can be fundamental for school counselors and the subject teachers in formulating and implementing the learning process, to reduce the effects of smartphone addiction, enhance their communication skills, and improve the learning efficiency through the use of the smartphone as learning media, instead of restraining the smartphone use.